Case Report: Exogenous insulin antibody syndrome complicated with chronic renal failure and long-term history of type 2 diabetes: report of two cases - Hu, Zhiwei; Huang, Xiaozhu; Pan, Jun; Dong, Hua (Frontiers in Endocrinology, 2025)
BackgroundInsulin autoimmune syndrome (IAS), a rare condition caused by an endogenous insulin-induced autoimmune reaction, is characterized by recurrent hypoglycemic episodes, positive insulin autoantibodies (IAAs), and high serum insulin levels. However, recent studies have demonstrated that exogenous insulin administration can also lead to similar clinical manifestations and have proposed the concept of non-classical IAS. This article reports two cases of exogenous insulin antibody syndrome (EIAS), analyzes their clinical features, and describes our therapeutic approach.Case presentationThe first patient was an 83-year-old male with a 15-year history of type 2 diabetes, while the second patient was an 86-year-old male with a 20-year history of type 2 diabetes. Both patients had a history of exogenous insulin use and chronic renal failure. On admission, they exhibited alternating episodes of hypoglycemia and hyperglycemia. Laboratory tests revealed hyperinsulinemia (insulin >600.00 μIU/ml in both patients), a dissociation phenomenon between blood insulin and C-peptide levels, and positive IAAs.ConclusionIn both patients, glycemic fluctuations resolved following insulin discontinuation and the initiation of dorzagliatin, confirming the diagnosis of EIAS. In type 2 diabetic patients with unexplained hypoglycemic and hyperglycemic episodes with a history of exogenous insulin use, pancreatic function and the autoimmune antibody spectrum should be comprehensively evaluated to rule out EIAS and provide an accurate diagnosis and guide treatment strategies.